Fabrication And Characterization Of Agar Based Anthropomorphic Ultrasound Breast Phantom - Foroozandehasl, Seyedeh Parisa (2012)

(untitled)
An anthropomorphic agar based breast phantom including tissue mimicking (TM) non adipose glandular tissue, TM fat and TM cyst was been fabricated. The fabricated phantom was characterized and the weight composition, temperature, frequency and time dependencies of the phantom were investigated. The sound speed and attenuation coefficient were measured by using the transmission substitution technique with three broadband transducers with 2.25, 5 and 10 MHz frequencies. Acoustic impedance, reflection coefficient and bulk modulus of fabricated breast phantom were also assessed.